2015
DOI: 10.1117/12.2077607
|View full text |Cite
|
Sign up to set email alerts
|

Medical image segmentation using object atlas versus object cloud models

Abstract: Medical image segmentation is crucial for quantitative organ analysis and surgical planning. Since interactive segmentation is not practical in a production-mode clinical setting, automatic methods based on 3D object appearance models have been proposed. Among them, approaches based on object atlas are the most actively investigated. A key drawback of these approaches is that they require a time-costly image registration process to build and deploy the atlas. Object cloud models (OCM) have been introduced to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
(41 reference statements)
0
1
0
Order By: Relevance
“…21, we showed that optimum object search can improve SOSM segmentation with a single model per object and, in Ref. 22, we presented a first comparison between FOSM and SOSM (without optimum object search) using a single model per object. This is the first time we compare FOSM and SOSMs by using multiple models per object as baseline and evaluate the optimum object search approach in depth.…”
Section: Introductionmentioning
confidence: 99%
“…21, we showed that optimum object search can improve SOSM segmentation with a single model per object and, in Ref. 22, we presented a first comparison between FOSM and SOSM (without optimum object search) using a single model per object. This is the first time we compare FOSM and SOSMs by using multiple models per object as baseline and evaluate the optimum object search approach in depth.…”
Section: Introductionmentioning
confidence: 99%